2005
DOI: 10.1007/s10526-005-3313-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Herbivore-induced Plant Volatiles Increase Field Captures of Parasitic Wasps

Abstract: Field evidence for attraction of parasitic wasps from the families Encyrtidae and Mymaridae to grapevines baited with synthetic versions of three herbivore-induced plant volatiles (HIPV) is presented. In a replicated experiment conducted in a juice grape vineyard, sticky cards in blocks baited with controlled-release dispensers of methyl salicylate (MeSA), methyl jasmonate (MeJA) or (Z)-3-hexenyl acetate (HA), trapped significantly greater numbers of Metaphycus sp. (Encyrtidae) than cards in unbaited blocks du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 22 publications
2
61
1
1
Order By: Relevance
“…Ibrahim et al [45] found that in Y-tube olfactometer tests with Cotesia vestalis the parasitoid of crucifer-feeding diamond back moth preferred odour of MeJA to filtered air. When released from traps MeJA and MeSA attracted parasitoids of the families Encyrtidae and Mymaridae to grapevines [46]. These observations indirectly suggest that MeJA treatment could have potential in attracting natural enemies of conifer seedling pests to intact plants if seedlings are treated before attack by pest insects and mites.…”
Section: Elicitor Impacts On Plant Voc Emissions and Natural Enemies mentioning
confidence: 86%
“…Ibrahim et al [45] found that in Y-tube olfactometer tests with Cotesia vestalis the parasitoid of crucifer-feeding diamond back moth preferred odour of MeJA to filtered air. When released from traps MeJA and MeSA attracted parasitoids of the families Encyrtidae and Mymaridae to grapevines [46]. These observations indirectly suggest that MeJA treatment could have potential in attracting natural enemies of conifer seedling pests to intact plants if seedlings are treated before attack by pest insects and mites.…”
Section: Elicitor Impacts On Plant Voc Emissions and Natural Enemies mentioning
confidence: 86%
“…In particular, these studies showed that (Z)-3-hexenyl acetate, farnesene, and methyl salicylate could be used to manipulate behavior of beneficial insects under field conditions. These three compounds were attractive to numerous predators and parasitoids; methyl salicylate attracted the broadest diversity of insects and farnesene the least (James 2005;James and Grasswitz 2005). However, all compounds attracted the mymarid Anagrus daanei and other Anagrus species, although this effect was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Thaler (1999) also reported increases in parasitism of S. exigua on induced plants versus controls. A series of field studies demonstrated that sachets of individual synthetic HIPVs could be used to attract and retain natural enemies in perennial crop systems (James 2003a,b;James and Price 2004;James and Grasswitz 2005). In particular, these studies showed that (Z)-3-hexenyl acetate, farnesene, and methyl salicylate could be used to manipulate behavior of beneficial insects under field conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations